Subdermal Silicone and Collagen Injection Effect on the Skin of Rats (Rattus norvegicus) on the Third Day After Injection - Janice Viary (Jurnal Sain Veteriner, 2022)
Collagen and silicone are substances commonly used as dermal filler in a number of beauty procedures. However, sometimes these chemicals cause unwanted side effects on the skin. The purpose of this research is to analyse the effect of collagen and silicone subdermal injection on rat skin as a model for human skin. Materials in this research are 9 Wistar rats (Rattus norvegicus) divided into three groups with a number of 3 rats in each group. The first control group (K) is not given any injections, while KI and KII are injected with 0,1 ml collagen and 0,1 ml silicone respectively. On the third day, all groups are observed for macroscopic changes. Skin samples are taken by necropsy and are made into slides using HE stain. All procedures done are approved by the ethics commission of LLPT, UGM, Yogyakarta with the certificate number 00024/04/LPPT/V/2019. The slides are observed under a microscope with 20x and 40x magnification. Any microscopic changes are noted, also epidermis and dermis lengths are measured. Mild hyperkeratosis, inflammation and proliferation of connective tissue are found. The measurements of the  epidermis and dermis are analysed using T-test independent method in the program Statistical Product and Service Solution (SPSS). The mean length of the epidermis is a little thicker than normal but is not significant (P>0,05). The results of this research show that the subdermal injection of 0,1 ml collagen and 0,1 ml silicone on rats do not cause significant macroscopic or microscopic changes.